2004
DOI: 10.1002/mus.20099
|View full text |Cite
|
Sign up to set email alerts
|

Reduced acetylcholine receptor density, morphological remodeling, and butyrylcholinesterase activity can sustain muscle function in acetylcholinesterase knockout mice

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…In the absence of ColQ as in the absence of AChE, AChR clusters are smaller and fragmented, but in contrast to ColQ mutant mice, the density of AChRs is decreased in adult AChE mutant mice (Xie et al, 2000;Adler et al, 2004). This last phenotype was only evident in mature synapses as neonatal AChE mutant NMJs were normal.…”
Section: Comparison Of Nmj Phenotypes Between Cholinesterase Mutantsmentioning
confidence: 99%
“…In the absence of ColQ as in the absence of AChE, AChR clusters are smaller and fragmented, but in contrast to ColQ mutant mice, the density of AChRs is decreased in adult AChE mutant mice (Xie et al, 2000;Adler et al, 2004). This last phenotype was only evident in mature synapses as neonatal AChE mutant NMJs were normal.…”
Section: Comparison Of Nmj Phenotypes Between Cholinesterase Mutantsmentioning
confidence: 99%
“…We aimed to determine whether LT would ameliorate the soleus muscle performance observed in congenital conditions with altered neuromuscular transmission and neuromuscular fatigability (tetanic fade). [11][12][13] For this purpose, we investigated two murine models with synaptic AChE deficiency: AChE KO and perlecan mutant mice. In a previous study we showed that there was soleus muscle weakness in AChE KO mice (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Absence or reduced level of acetylcholinesterase (AChE) at the neuromuscular junction impairs neuromuscular functioning, because AChE hydrolyzes acetylcholine (ACh) and prevents ACh accumulation with desensitization of ACh receptors. 11 Accordingly, muscles from knockout (KO) AChE mice are unable to maintain force production in response to repetitive nerve stimulation, regardless of frequency. 11,12 Perlecan mutant mice were recently generated by introducing a missense mutation into the Hspg2 gene that encodes perlecan.…”
Section: Muscle Nerve 45: 567-577 2012mentioning
confidence: 99%
See 2 more Smart Citations